2012
DOI: 10.1016/j.rmed.2012.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of CD103 expression in bronchoalveolar lymphocytes in sarcoidosis

Abstract: Assessment of CD103 expression in BALF CD4(+) T-lymphocytes may be a reliable tool for sarcoidosis diagnosis, independently of CD4(+)/CD8(+) ratio, pointing out the relevance of evaluating the CD103(+)CD4(+)/CD4(+) ratio in the ILD diagnostic work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
2
27
1
Order By: Relevance
“…Four studies analyzing the CD103+CD4+/CD4+ ratio in sarcoidosis, either alone or in combination with the CD4+/CD8+ ratio, have been previously performed [15,16,17,18]. The cut-off values defined in those studies to discriminate between sarcoidosis and other diagnoses were applied to our study population for comparison (table 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies analyzing the CD103+CD4+/CD4+ ratio in sarcoidosis, either alone or in combination with the CD4+/CD8+ ratio, have been previously performed [15,16,17,18]. The cut-off values defined in those studies to discriminate between sarcoidosis and other diagnoses were applied to our study population for comparison (table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Kolopp-Sarda et al [15] found that a high CD4+/CD8+ ratio combined with a low CD103+CD4+/CD4+ ratio allowed to distinguish sarcoidosis from other ILDs with a 96% sensitivity. Similarly, Mota et al [17] found a 98% sensitivity. However, two other studies showed a lower performance of the CD103+CD4+/CD4+ ratio as a diagnostic marker for sarcoidosis [16,18].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Sarcoidosis is neither a malignant nor an autoimmune disease, however, both genetic and environmental factors seem to play a role, and reaction to an unidentified antigen is suspected, despite the cellular immune response occurs in the absence of a clearly defined immunological target [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%